The Effect of Attitude, Subjective Norm, and Perceived Behavioral Control on Purchase Intention of Halal Cosmetic Products with Country Of Origin and Brand Equity as Moderating (Survey on Muslim Women in Semarang District) - Sania Khaulia (Social Science Studies, 2021)
This study is to measure the effect of attitude, subjective norm, perceived behavior control on purchase intention of halal cosmetic products with country of origin and brand equity as moderating variables. This study uses quantitative research using multiple linear regression analysis and Moderated Regression Analysis (MRA). Data collection techniques by distributing questionnaires. Samples were taken as many as 156 respondents who were given to Muslim women who live in Semarang Regency. The results showed that there was an influence between attitude, subjective norm, perceived behavior control on the purchase intention of halal cosmetic products. The results of Moderated Regression Analysis (MRA) show that the country of origin cannot moderate the effect of attitude, subjective norm, perceived behavior control on purchase intention of halal cosmetic products. Meanwhile, brand equity can moderate the effect of perceived behavior control and cannot moderate the influence of attitude, subjective norm on purchase intention of halal cosmetic products.